Understanding the problem of knowledge sharing. (19th April 2004) - Krogh, Georg von
Much research on knowledge management has recognised the difficulty of sharing knowledge in organisations. Building on previous research, this paper suggests the problem of knowledge sharing stems from distributed and diverse interests of organisational members, and that it can be understood as a problem of creating collective action. The paper indicates some possible solutions to the problem of knowledge sharing, and generates a number of corresponding research questions that may trigger much needed work on knowledge sharing in organisations.